From independence to the Euro introduction: varieties of capitalism in the Baltic States - Ralph Wrobel (Central and Eastern European Journal of Management and Economics, 2015)
The Baltic States, Estonia, Latvia and Lithuania, are very successful in transformation. From 1991 to 2015 they regained independence and transformed their economies from socialist central planning into functioning mar-ket economies, joined the EU in 2004 and became member of the Euro zone. Estonia introduced the Euro al-ready in 2011 while Latvia followed in 2014 and Lithuania in 2015. Thereof follow two questions. First, why all three Baltic countries are so successful? And secondly, do we really find everywhere the pattern of the “Shining star” Estonia, followed by Latvia and at least Lithuania? According to modern Varieties of Capitalism theory all three economies can be classified as Central and Eastern European Countries in the style of Liberal Market Economies (CEEC-LME). As can be shown, there are also differences in the institutional setups of all three Baltic States. During the period of transformation a pattern of Estonia followed by Latvia and at least Lithuania evolved which is also reflected by the sequence of joining Euro area. But institutional patterns are not determined in the long run. Since the crisis of 2008/09 the pattern within the Baltics changed. While Estonia remains on the first rank Lithuania overtook Latvia in terms of growth and wealth. Deregulation in Lithuania – which may be observed by the development of the Economic Freedom Index of the Heritage Foundation within the last ten years – may be the main reason. But also, the low sophistication of the Lithuanian banking system as well as Latvia's massive suffering from the crisis may explain the last change of the pattern in the Baltics. There are several possibilities to illustrate the different paths of development of the Baltic States. While Geography Hypothesis is not able to explain the differences, the extractive political institutions in Estonia and Latvia can illustrate the lead of both countries in contrast to Lithuania till the crisis in 2008/09. Additionally, different basic values in all three Baltic States are responsible for the different developmental paths. They can also be traced back to the different history and culture of the three Baltic countries.
Keywords: P16; P20; P51; 330; Baltic States; VoC; Euro-introduction; Baltikum; Euro